Rancang Bangun Aplikasi Management Projection Control Sheet Penjualan Produk Sembako Berasis Web Menggunakan Metode Extreme Programming (Studi Kasus: Toko Suyudi Sembako) - Sahlan, Dede (CV. Shofanah Media Berkah, 2023)
The Management Projection Control Sheet (MPCS) is an important factor for the Suyudi Sembako Shop to ease operational work, this is related to errors in product data collection at the Suyudi Sembako Shop. Therefore, it is necessary to have special data collection for the projection of product sales data stock so that work activities can run effectively. One way that can be done to achieve good product sales projections is to use computer technology which is implemented with the web-based MPCS application. At the Suyudi Sembako Shop used in the process of sales projections and reporting reports still use manual records that have an ineffective and inefficient impact. Besides that, the risk of error and loss of data is getting bigger. Based on the above problems, a projection of the sale of web-based food products is made with research methods used in data collection, namely: observation methods, interviews and libraries. While the development of software using extreme programming. With the creation of a web-based MPCS application can provide convenience in the process of projection of product sales stock, which helps employees in data projections, data search and quick sales reports.